Safety and immunogenicity of the inactivated whole-virus adjuvanted COVID-19 vaccine VLA2001: A randomized, dose escalation, double-blind phase 1/2 clinical trial in healthy adults. Issue 3 (September 2022) - Lazarus, Rajeka; Taucher, Christian; Brown, Claire; Čorbic Ramljak, Irena; Danon, Leon; Dubischar, Katrin; Duncan, Christopher J.A.; Eder-Lingelbach, Susanne; Faust, Saul N.; Green, Christopher; Gokani, Karishma; Hochreiter, Romana; et al.
Highlights: VLA2001 is a whole-virus, inactivated, adjuvanted COVID-19 vaccine candidate. VLA2001 induces neutralizing antibodies and T-cell responses against COVID-19. VLA2001 is well tolerated in adults aged 18–55 years, with no safety signal of concern being identified. Comparison of three different dose levels allowed identification of optimum dosage for further clinical investigation. Summary: Objectives: We aimed to evaluate the safety and optimal dose of a novel inactivated whole-virus adjuvanted vaccine against SARS-CoV-2: VLA2001. Methods: We conducted an open-label, dose-escalation study followed by a double-blind randomized trial using low, medium and high doses of VLA2001 (1:1:1). The primary safety outcome was the frequency and severity of solicited local and systemic reactions within 7 days after vaccination. The primary immunogenicity outcome was the geometric mean titre (GMT) of neutralizing antibodies against SARS-CoV-2 two weeks after the second vaccination. The study is registered as NCT04671017. Results: Between December 16, 2020, and June 3, 2021, 153 healthy adults aged 18–55 years were recruited in the UK. Overall, 81.7% of the participants reported a solicited AE, with injection site tenderness (58.2%) and headache (46.4%) being the most frequent. Only 2 participants reported a severe solicited event. Up to day 106, 131 (85.6%) participants had reported any AE. All observed incidents were transient and non-life threatening in nature. Immunogenicity measured at 2 weeks after completion of the two-dose priming schedule, showed significantly higher GMTs of SARS-CoV-2 neutralizing antibody titres in the highest dose group (GMT 545.6; 95% CI: 428.1, 695.4) which were similar to a panel of convalescent sera (GMT 526.9; 95% CI: 336.5, 825.1). Seroconversion rates of neutralizing antibodies were also significantly higher in the high-dose group (>90%) compared to the other dose groups. In the high dose group, antigen-specific IFN-γ expressing T-cells reactive against the S, M and N proteins were observed in 76, 36 and 49%, respectively. Conclusions: VLA2001 was well tolerated in all tested dose groups, and no safety signal of concern was identified. The highest dose group showed statistically significantly stronger immunogenicity with similar tolerability and safety, and was selected for phase 3 clinical development.